2022
DOI: 10.21203/rs.3.rs-2227716/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Responses of photosynthesis and chlorophyll fluorescence during light induction in different seedling ages of Mahonia oiwakensis

Abstract: Background The aim of this study was to determine the actual state of the photosynthetic apparatus and exhibit distinguishable differences in the chlorophyll fluorescence (ChlF) components in different seedling ages of M. oiwakensis plants subjected to different light intensity (LI), that reflected their adaptability to their habitats and how they responded to LI changes. Potted 6-month-old greenhouse seedlings and field collected 2.4-year-old seedlings with 5 cm heights were selected and randomly separated i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Scholars have conducted quantitative experiments to examine the impact of meteorological factors on the fruit setting rate of passion fruit (Zheng & Wei, 2018;Masakazu & Hiroshi, 2022), and have determined that excessive temperatures can decrease the fruit setting rate (Wang et al, 2022;Masakazu & Hiroshi, 2022). Additionally, some scholars have investigated the effects of extreme weather on passion fruit (Xiao et al, 2021) and have observed that frost resulting from extremely low temperatures often leads to varying degrees of damage to the growth and development of the fruit (Chen et al, 2022). A number of foreign scholars studied the relationship between passion fruit and climate factors by using stepwise backward reasoning method (Matsuda & Higuchi, 2020b) and quantitative analysis (Shimada et al, 2020), and found that excessive temperature would affect the normal flowering of passion fruit and reduce the sugar content of passion fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have conducted quantitative experiments to examine the impact of meteorological factors on the fruit setting rate of passion fruit (Zheng & Wei, 2018;Masakazu & Hiroshi, 2022), and have determined that excessive temperatures can decrease the fruit setting rate (Wang et al, 2022;Masakazu & Hiroshi, 2022). Additionally, some scholars have investigated the effects of extreme weather on passion fruit (Xiao et al, 2021) and have observed that frost resulting from extremely low temperatures often leads to varying degrees of damage to the growth and development of the fruit (Chen et al, 2022). A number of foreign scholars studied the relationship between passion fruit and climate factors by using stepwise backward reasoning method (Matsuda & Higuchi, 2020b) and quantitative analysis (Shimada et al, 2020), and found that excessive temperature would affect the normal flowering of passion fruit and reduce the sugar content of passion fruit.…”
Section: Introductionmentioning
confidence: 99%